ON THE USE OF THE GRAPHING CALCULATOR IN SOME HIGH SCHOOL MATH TOPICS (American Journal of Interdisciplinary Research and Development, 2024)
This paper investigates Desmos Graphing Calculator's effectiveness as a teaching tool for high school math (academic lyceum). It showcases Desmos' applications for both senior and junior students. For seniors, it demonstrates how Desmos tackles continuous random distributions, solving for probabilities and moments (mean, median, etc.) of a given probability density function. For juniors, it exemplifies how Desmos aids in real-world data modeling with sine functions, fitting a curve to Tashkent's monthly temperature data. While initial syntax learning is required, Desmos' benefits outweigh the effort, promoting visualization, calculation speed, and ultimately, enhanced student understanding and engagement.